Minority Shareholdings in European Union Merger Control - Balaba, Jeaneth Michelle Labis (Archives of Business Research, 2017)
From the perspective of competition policy, which looks into how the competitive field in industry markets are enhanced or threatened, mergers and acquisitions are closely observed especially with regard to how they disrupt the level playing field of otherwise competitive industries. That is, there are laws in many countries that enforce anti-trust competition policies and the application of these policies are strictly enforced in many major mergers and acquisitions in market-based nation-state economies and regional economies such as the European Union and its component countries. This research looks into merger control in the European Union and the important focus that the EU has put on minority shareholdings in mergers and acquisitions and full joint ventures. Specifically, the central issue is the lack of mechanism at the EU level to effectively deal with undue decisive influence that minority shareholdings bring to the table of merger strategic, and therefore, competitive decision-making.